Estudio de factibilidad de la creación de una empresa productora y comercializadora de máquinas automatizadas preparadoras y expendedoras de empanadas en Bogotá, D.C. (2018)
This feasibility study is carried out in order to create a production and trading company of vending machines that automatically prepare and sell empanadas in Bogotá D.C., the idea start with the initiative for consolidate the life business project of the author and her family.